Exploration of Students' Experiences in Using a Starter Wiring Simulator in Automotive Electricity Learning - Firman Nur Falah; Muhammad Atala Abka; Wahid Munawar (International Journal of Technology and Education Research, 2026)
This study aims to investigate students' experiences in utilizing a starter wiring simulator during the automotive electrical learning process at SMKN 1 Leuwidamar. This study adopted a descriptive qualitative approach with a sample of 11th-grade students majoring in Motorcycle Engineering and Business. Data were collected through participant observation, semi-structured interviews, documentation, and practical assessments. The study findings indicate that the use of a starter wiring simulator contributed to improving students' understanding and practical skills. The percentage of students who successfully assembled the starter circuit increased from 40% to 70%, while the average time to complete the circuit decreased from 27.4 minutes to 18.6 minutes. In addition, students found it easier to understand component functions and perform troubleshooting, and were more active and interested during the learning process. The level of student satisfaction with the use of the simulator was also in the good category. Therefore, the starter wiring simulator can be an effective learning tool to improve the quality of automotive electrical education in vocational high schools.